Development Of Interactive Card-Based Pop-Up Media With A Noble Moral Theme To Increase Student Learning Interest - Nuraeni, Fahrida; Arqam, Mhd. Lailan; Widodo, Hendro (Early Publishing, 2026)
This study aims to develop interactive card-based pop-up media with the theme of Exemplary Morals (honesty) to increase the learning interest of second-grade students at SD Negeri Kutogiri. This research is driven by the low level of student interest in learning, which is only 56%, as well as the difficulties students experience in understanding abstract moral concepts thru conventional teaching media.This study uses the ADDIE development model with a Mixed Methods approach. The participants included two expert validators, one Islamic Religious Education teacher, and 22 students. Data were collected thru validation instruments, response questionnaires, and a One-Group Pretest-Posttest design, then analyzed using paired t-tests and N-gain scores. The results show that the developed media is categorized as very feasible (91.96%) and very practical (93.75%). The application of the media significantly increased students' learning interest (p < 0.001), with the average score rising from 66.77 to 79.77 and an N-gain of 0.40 (moderate category). The interactive simulation feature successfully crystallized the value of honesty, enhancing student attention and their active engagement in the learning process.